PENGARUH LINGKUNGAN KELUARGA DAN PEMANFAATAN INTERNET SEBAGAI SUMBER BELAJAR TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMANEGERI 5 SEMARANG - Nugrahini, Rizki Widya; Margunani, Margunani (Dinamika Pendidikan, 2015)
The objectives of this research are to identify the effect of family environment and the internet usage as learning source simultanly or partially on economics learning motivation. Population of SMA Negeri 5 Semarang students (IIS/Social Program) are 192, 66 students are samples. Data collecting method uses questionnaire. Data analyzing uses descriptive and double equal regression analyzing. Descriptive analyzing percentage: high learning motivation (62%), good family environment (61%), good internet usage as learning source (67%). The result of this research is family environment and the internet usage as learning source simultanly give positive effect and significant to economics learning motivation (39,8%). Partially, family environment give positive effect and significant to economics learning motivation (17,2%), the internet usage as learning source give positive effect and significant to economics learning motivation (8,6%). The conclusion is family environment and the internet usage as learning usage give positive effect and significant to economics learning motivation at SMA Negeri 5 Semarang simultanly and partially. As suggestion, family environment should keep the good condition, the internet usage as learning media should be more optimal, family hopefully always keep condusive, calm, comfortable and enjoyable condition, students should increase the intensity of accessing economics information through the internet.